Strategi Gerakan Sosial Politik Masyarakat terhadap Tambang Pasir di Desa Sejagung Kabupaten Banyuasin - Putri Puspita Sari; Reni Apriani; Ainur Ropik (Penerbit Jurnal Indonesia, 2025)
Sand mining in Sejagung Village, Rantau Bayur District, Banyuasin Regency, has caused significant social and environmental impacts, ranging from riverbank erosion, water pollution, and machine noise to the loss of community comfort. This study aims to analyze the strategies of community socio-political movements in responding to sand mining activities. Using a qualitative case study method, data were collected through interviews, observations, and documentation involving community leaders, village officials, and affected residents. The findings reveal that the community movement emerged from disappointment toward the company and the village government, both perceived as neglecting residents’ interests. Through the forum Masyarakat Sejagung Bersatu (United Sejagung Community), residents employed demonstrations, deliberations, and media as their main strategies to fight for the right to a healthy environment. An analysis using Alain Touraine’s theory shows that the movement was shaped through the dimensions of identity, opposition, and totality, signifying both ecological and political resistance against corporate dominance and the village government’s lack of transparency. This study concludes that the socio-political movement strategies of Sejagung villagers represent a collective struggle that not only addresses local issues but also connects with broader concerns of environmental sustainability, social justice, and natural resource governance.